O discurso religioso da Pastoral Escolar no Colégio Sagrado Coração de Jesus-SP para as crianças de três a seis anos de idade - Santos, Giuliane Ciniciato Gonçalves dos (2020)
In view of the countless studies already published on Catholic education, religious teaching or religious discourse, as well as the importance of playfulness in the education of children, in this study, the analysis and verification of religious discourse used in a Catholic confessional teaching institution, Colégio Sagrado Coração de Jesus-SP, for School Pastoral Care with children from three to six years old. A literature review was taken as a starting point, for a better understanding, on Catholic education and the Clelian charism, which guides the institutional mission of the college, was presented. Then, it was understood the importance of playfulness and, using a doll - Clelinha -, it was observed the religious experience lived by these children, originating in the religious discourse of the School Pastoral. Finally, it was possible to understand that it is not just a religious discourse that guarantees rules of experience, but an experience of the charism that is translated into a religious discourse by the School Pastoral